Implementation Support Mission - Aide Memoire March 2022 - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
From March 21-25, 2022, the World Bank and the International Center for Tropical Agriculture (CIAT) jointly undertook an Implementation Support Mission (ISM) for the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) (P173398) in Accra, Ghana. The mission coincided with cluster and management meetings of the AICCRA project involving multiple partners from the AICCRA network (participant list included in Annex 1).